Екуменічні ініціативи Митрополита Андрея Шептицького - Волинець, Оксана; Volynets, Oksana (Lviv Politechnic Publishing House, 2017)
Проаналізовано теоретичний та практичний аспекти екуменічної діяльності Митрополита УГКЦ Андрея Шептицького. Досліджено праці Митрополита про екуменічні ідеї та можливості проголошення Патріархату Української Церкви.

The article analyzes the work of Metropolitan Andrey Sheptytsky devoted to the problem of unification of Ukrainian churches. The Metropolitan’s view on the issues of separation caused by foreign influences on historical, cultural and mental development of the Ukrainian people is being researched. It turns out that A.Sheptytsky put great hopes in the reunification of the Ukrainian Greek-Catholic Church, which, being combined dogmatically with the West and ritually with the East, was objectively intended to work. Practical activity of A. Sheptytsky is being analyzed aiming at organization of structures, including: the Order of Studites, the Eastern branch of the order of Redemptorists, Theological Academy which was assigned the task of uniate labour based on a method of dialogue. Ecumenical initiatives of Metropolitan on the territory of Western Europe and Russia are exposed. Particular attention is paid to A. Sheptytsky’s ecumenical dialogue with the hierarchs of the Orthodox Church and his arguments stating the importance of unity for all Ukrainian people. In this context, Metropolitan’s position regarding the declaration of the Patriarchate of the Ukrainian Church, which was quite ambiguous, is being analyzed. On the one hand, the formation of the Patriarchy could lead to a complete reunion with the Universal Church, and on the other, there was a potential threat of schism within the Ukrainian Church.
The ecumenical initiatives of Metropolitan Andrey Sheptytsky
Keywords: Церква; унія; діалог; екуменічний рух; Патріархат; Church; union; dialogue; ecumenical movement; Patriarchy; 261.6